In vivo antioxidant and hepatoprotective effects of methanolic extract of dioclea reflexa seed in rats following acute or chronic liver injury (Bangladesh Journal of Pharmacology, 2014)
Methanolic extract of Dioclea reflexa seed was investigated following acute or chronic carbon tetrachloride intoxication in male albino rats. In the acute experiment, rats were pre-treated with extract at 5 mg/kg for three days before administration of carbon tetrachloride(0.6 mL/kg) while in the chronic model, rats received extract at 2.5 mg/kg for 12 consecutive days with 72 hourly administration of carbon tetrachloride at 0.3 mL/kg. In both models, the levels of transaminases and malondialdehyde were significantly (p